A person-centred model of HIV nursing care: translating principles into practice - Michelle Croston; Steve Callaghan; Justine Mellor; Eileen Nixon (Frontiers in Health Services, 2026)
This paper presents the development and application of a Person-Centred Model of HIV Nursing Care created by the National HIV Nurses Association (NHIVNA). The model responds to the evolving complexities of HIV care and the need to articulate and standardise the nursing contribution within the HIV care continuum. Developed collaboratively with people living with HIV, clinical nurse specialists, and academics, the model provides a structured, person-centred framework to guide high-quality nursing care across diverse clinical contexts. Objectives The model aims to: Enhance care quality and patient experience through empathy, relational practice, and co-designed care. Support nurses' professional development and reduce variation in care. Promote workforce sustainability by fostering role clarity, engagement, and shared understanding of the nurse's value in the care pathway. Implementation Grounded in McCormack and McCance's person-centred nursing framework, the model adapts these principles to the unique psychosocial dynamics of HIV care, including stigma and self-stigma. Central to the model is empathy and the therapeutic nurse–patient relationship, which enables open communication, psychological safety, and holistic care that addresses physical, emotional, and social dimensions of wellbeing. Implementation of the model of care is supported by a reflective learning workbook designed to integrate the model into clinical practice and continuous professional development. The workbook encourages reflective dialogue, shared learning, and professional growth, aligning with values-based leadership and person-centred culture. Conclusion The paper concludes that embedding a person-centred approach within HIV nursing enhances care consistency, improves workforce morale, and builds a sustainable, compassionate culture capable of adapting to the future needs of people living with HIV.